Identification of Culinary Potential in Neglasari Village, Cisompet, Garut - Irfansyah; Hidayat, Nova Maulidian; Purnama, Rusna; Resmi, Irma Citra; Nurizki, Reza (Journal of Tourism, Hospitality and Travel Management, 2023)
This study aimed to identify the natural resources from agriculture that could develop to be culinary tourism in Desa Neglasari, Kec. Cisompet, Kab. Garut. The study of documentation, field observations, and in-depth interviews are used in this research and analyzed by a qualitative descriptive analysis. Four excellent products can be processed into culinary products such as jackfruit, soursop, banana, and brown sugar. The fourth of an excellent product that can be processed into various foods and beverages with good taste, excellent shape, and a good texture of the culinary product. Based on this fact in Desa Neglasari, Kec. Cisompet, Kab. Garut potentially developed alternative tourism, which is a culinary tour. This is important because of not only the development of diversified tourism products but, at the same time, grow the creative economy among members of society. To realize the need for special attention of local government, tourism entrepreneurs, and communities (farmers).